مسؤولية مراجع الحسابات في الجزائر و أثره على مصداقية التقارير وفق معايير المراجعة الدولية - علاق, فاطمة (جامعة الوادي - University of Eloued, 2019)
تهدف هذه الدراسة على التعرف لمسؤوليات مراجع الحسابات في الجزائر، وأثر هذه المسؤوليات على مصداقية التقارير المالية، بالاعتماد على المتغيران المستقلان الأول متمثل في المسؤولية القانونية التي نص عليها القانون ( 01/10المسؤولية المدنية، المسؤولية الجزائية، التأديبية) والثاني متمثل في المسؤولية المهنية من خلال مقدرة مراجعي الحسابات الالتزام بمعايير المراجعة وقواعد السلوك المهني، ومصداقية التقارير المالية كمتغير تابع. وقد أظهرت الدراسة بأن تحمل مراجعي الحسابات لمسؤولياتهم القانونية والمهنية تؤثر في مصداقية التقارير المالية، كما أثبتت وجود فروق ذات دلالة إحصائية حول التزام مراجع الحسابات لمسؤولياته تعزى للمتغيرات الشخصية (المؤهل العلمي، الفئة، سنوات الخبرة في العمل،) كذا للمتغيرات الاسمية (مسؤوليات مراجع الحسابات القانونية، الالتزام بالمعايير الشخصية، الالتزام بمعايير العمل الميداني، الالتزام بمعايير اعداد التقرير، الالتزام بقواعد وآداب المهنة)، كما تبين الدراسة وجود فروق ذات دلالة إحصائية حول مدى مصداقية التقارير المالية تعزى لمتغير فئة مراجعي الحسابات وفئة مستخدمي التقارير المالية. ومن خلال النتائج المتوصل إليها توصي الطالبة بما يلي - إصدار مقررات جديدة لتنظيم مهنة المحاسبة والمراجعة لتدعيم القانون 01/10يعمل على الارتقاء بالمهنة وتحديد أكثر للمسؤوليات القانونية بشيء من التفصيل؛ - توسيع اختصاصات وحدة الرقابة على جودة أعمال مراجعي الحسابات بهيئة الرقابة المالية بهدف التأكد من التزام المراجعين بالمعايير المهنية وقواعد وآداب السلوك المهني عند مراجعة التقارير المالية. - انشاء هيئات مهنية جهوية تكون تابعة للمصف الوطني للخبراء المحاسبين أو الغرفة الوطنية لمحافظي الحسابات بزيادة الاتصال مع مستخدمي التقارير المالية بهدف تحسين إدراكهم لحدود مسؤولية المراجع. - اعتماد نظام كامل للمسؤولية المهنية من حيث قواعد ومعايير للمراجعة تتلاءم والبيئة الجزائرية، والتشجيع على عقد دورات تكوينية محلية ودولية للتعريف على قواعد هذه المهنة..This study aims to identify the responsibilities of the Auditor in Algeria and the impact of these responsibilities on the credibility of the financial reports, relying on the first two independent variables of the legal liability provided by law 10/01 (civil liability, criminal liability, Disciplinary) The second is professional responsibility through the ability of auditors to comply with auditing standards and professional conduct, and the credibility of financial reports as a dependent variable. The study showed that auditors ' accountability for their legal and professional responsibilities affects the credibility of financial reports, and that there are statistically significant differences about the auditor's commitment to his responsibilities due to personal variables (qualification, category, years of work experience), as well as For nominal variables (legal auditor's responsibilities, compliance with personal standards, compliance with field work standards, adherence to reporting standards, compliance with professional rules and ethics), the study also shows statistically significant differences on the reliability of financial reporting Attributed to the variable of the auditor category and the category of users of financial reports. Through the findings, the student recommends the following: - Promulgation of a news Decisions to regulate the accountancy and auditing profession in order to strengthen law 10/01, which will promote the promotion of the profession and further define the legal responsibilities in some detail; - to expand the competencies of the auditor's quality control unit in the Financial Supervision authority with a view to ensuring that the auditors adhere to professional standards, rules and professional ethics when reviewing financial reports. - The establishment of regional professional bodies affiliated with the National auditor or the National Chamber of Auditors to increase contact with the users of financial reports in order to improve their awareness of the limits of the responsibility of the reviewer. - The adoption of a complete system of professional responsibility in terms of rules and standards of auditing that are compatible with the Algerian environment, and encourage the holding of local and international training courses to publicize the rules of this profession.
دراسة ميدانية-
أطروحة دكتوراه تخصص محاسبة و تدقيق في العلوم الاقتصادية و التجارية و علوم التسيير
Keywords: مسؤوليات مراجع الحسابات ، المسؤولية القانونية ، المسؤولية المهنية ، مصداقية التقارير المالية; Auditor's responsibilities, legal responsibility, professional responsibility, credibility of financial reporting.